Rowing performance and rowing technique of German junior women in the eight from 2001-2011 - Mattes, K.; Manzer, S.; Boehmert, W. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
For several years, regularly in June / July 2000-m race tests in the eight (8+) were performed with the best athletes of each year in preparation for the World Junior Championships (WJC). The data represent the individual rowing technique and the transformation of the motor abilities into rowing performance under the specific conditions of big boats. The cross-sectional data show what kind of medium-term development was completed from 2001-2011 in order to show trends for the junior women as well as for setting a benchmark for powerful rowers. Methods: Each year two 8+ with junior women (N = 156; body height 1.79 ± 0.05m, body mass 70.2 ± 5.8kg) were measured over 2000-m races on the same regatta course in "Berlin Gruenau". The race boat was equipped with a mobile measuring system (Böhmert & Mattes, 2003) that captured the inboard handle force as the oar bending moment, with a strain gauge (resolution 0.25N), and the oar angle with a high-resolution magnetic field sensor that is attached to the gate pin (resolution 0.1°). Based on the data, the inboard handle power per stroke (Pih) and its components force (Fih), velocity (vih) and stroke length (sl) were determined. The 2000-m race time from the finals of the WJC in the 8+ was taken as external criteria. For the evaluation a linear regression analysis was calculated. On the basis of the results, different performance groups were formed. Results: The race times of the winner and the German crews at WJC in the 8+ decreased approximately 1.5s/year during the period studied. The decrease in the body height of the German junior women was not significant in comparison to the body mass. At the same time the stroke rate remained comparable, however a significant increase in the Pih (1.1W/year) and the Fih (1.2N/year) with significant decrease of the sl (-0.2°/year) was found. Based on Pih six performance groups from international level (225 ± 6W) until national level (164 ± 2W) were formed. Discussion: The positive development of the external criteria (race time) corresponds with the increase of the Pih over the 2000m. Since performance development is based on crosssectional data, various reasons are responsible for it. The trend can be attributed to an improved rowing technique and a more effective transformation of motor abilities in rowing performance, but without making a clear distinction between current exercise-induced effects or selection effects. The individual rowing power can be better assessed on the basis of the new performance groups.